HUBUNGAN DUKUNGAN SUAMI DENGAN PEMINATAN KB PASCA PERSALINAN IUD DIWILAYAH PUSKESMAS PALERAN - Khasanah, Siti Nur; Palupi, Jenie; Gumiarti, Gumiarti (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Postpartum family planning (IUD) is still rarely sought after by postpartum mothers. The low usage rate is 62 acceptors (16.5%) of the target of 338 acceptors (65%) of new postpartum family planning in the Paleran Community Health Center area. One form of husband's participation in the use of family planning is supporting his wife in choosing a family planning tool. Husband's support is one of the factors that can influence the mother's interest in using postpartum IUD family planning. The purpose of this study was to determine the relationship between husband's support and interest in postpartum IUD family planning. This study used a correlational analytical study type with a cross-sectional design with a population of 155 pregnant women, a sample of 112 pregnant women, a simple random sampling technique and the test used was chi square. The results showed that 56.2% of respondents received husband's support, 75.9% of respondents were not interested in postpartum IUD family planning. The results of the test analysis obtained a p-value of 0.001 <? 0.05. There is a relationship between husband's support and interest in postpartum IUD contraception. It is recommended that husbands participate in their wives' choice of contraception after giving birth and that health workers increase counseling on postpartum IUD contraception. ABSTRAKKeluarga Berencana pasca persalinan IUD masih jarang diminati oleh Ibu pasca salin, Angka penggunaaannya yang rendah yaitu 62 akseptor (16,5%) dari target 338 akseptor (65%) KB baru pasca persalinan  diwilayah Puskesmas Paleran. Salah satu bentuk partisipasi suami dalam penggunaan alat KB adalah mendukung istri dalam memilih alat KB.Dukungan suami menjadi salah satu faktor yang bisa mempengaruhi minat ibu untuk menggunakan KB pasca persalianan IUD. Tujuan penelitian ini untuk mengatahui hubungan dukungan suami dengan peminatan KB pasca persalinan IUD. Penelitian ini menggunakan jenis penelitian analitik korelational dengan desain cross sectional dengan jumlah populasi 155 ibu hamil, jumlah sampel penelitian 112 ibu hamil, teknik sampling simple random samping dan uji yang digunakan adalah chi square. Hasil 56,2 % responden  mendapat dukungan suami, 75,9 % responden tidak berminat KB pasca persalinan IUD, Hasil analisis uji didapatkan  p-value 0,001 < ? 0.05. Terdapat hubungan dukungan suami dengan peminatan KB pasca persalinan IUD, disarankan kepada  suami ikut serta dalam pemilihan KB pada istrinya setelah melahirkan dan tenaga kesehatan meningkatkan penyuluhan tentang KB pasca persalinan IUD